2002
DOI: 10.1021/ja017873t
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Mediated Cycloaromatization of Acyclic Enediynes and Dienynes at Ambient Temperature

Abstract: The ruthenium(II) cation, [Cp*Ru(NCMe)3]OTf (4), triggers the Bergman cycloaromatization of acyclic endiynes at room temperature in THF solvent. Treatment of 1,2-di(1-alkynynyl)cyclopentenes (13-Me, alkynyl = propynyl; 13-Prn, alkynyl = pentynyl; 13-Bui, alkynyl = 4-methyl-pent-1-ynyl) with 4 in THF solvent at room temperature gives rise to the ruthenium arene complexes: [Cp*Ru{(3a,4,5,6,7,7a-eta)-2,3-dihydro-5,6-dialkyl-1H-indene}]OTf (15-Me, alkyl = methyl, 64% yield; 15-Prn, alkyl = n-propyl, 73% yield; 15-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…O'Connor et al [118] showed that stable enediynes 205 undergo cycloaromatization at 23oC in the presence of catalyst 207 in THF to give ruthenium naphthalene complexes 206 in good yields (Scheme 60). O'Connor et al [118] showed that stable enediynes 205 undergo cycloaromatization at 23oC in the presence of catalyst 207 in THF to give ruthenium naphthalene complexes 206 in good yields (Scheme 60).…”
Section: äääääääääääämentioning
confidence: 99%
“…O'Connor et al [118] showed that stable enediynes 205 undergo cycloaromatization at 23oC in the presence of catalyst 207 in THF to give ruthenium naphthalene complexes 206 in good yields (Scheme 60). O'Connor et al [118] showed that stable enediynes 205 undergo cycloaromatization at 23oC in the presence of catalyst 207 in THF to give ruthenium naphthalene complexes 206 in good yields (Scheme 60).…”
Section: äääääääääääämentioning
confidence: 99%
“…102,103 In fact, only recently have the electron withdrawing effects at the alkyne termini (i.e. lowering of the cyclization transition state energy) 85 and vinyl (i.e.…”
Section: Electronic Control Of Metalloenediyne Cyclizationmentioning
confidence: 99%
“…Analogously, OConnor et al have also shown ambient temperature enediyne activation through p complexation of the alkynes with Ru II or Fe II . [13] Although chemically facile, both methods necessitate either specific alkyne functionalization or unfavorable conditions to remove the activating metal fragment, neither of which are congruent with the efficient synthesis of extended porphyrin constructs.…”
mentioning
confidence: 99%